Strengthening Active Physical Education Learning Through a PJOK Trofeo Program: a Service-Learning Approach with Pre-Service Teachers at SD Citra Bakti - Nikodemus Bate; Bernabas Wani; Josep Marsianus Rewo; Yanuarius Ricardus Natal; Agustina Meo; Yohanes Paulus De Brito Naru (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aimed to enhance active learning and sportsmanship in elementary physical education through the implementation of a structured PJOK Trofeo model supported by pre-service teachers (PLP students). Conducted at SD Citra Bakti, the program adopted a service-learning framework integrating collaborative mentoring among lecturers, pre-service teachers, and school teachers. The intervention was implemented in four stages: needs assessment, collaborative design, structured Trofeo-based activities, and reflective evaluation. Data were collected using observation sheets assessing student participation and sportsmanship indicators, complemented by reflective reports from pre-service teachers. The results demonstrated a significant increase in active participation (from 62% to 85%) and improvements in sportsmanship indicators, including fair play and teamwork. Furthermore, pre-service teachers showed enhanced pedagogical competence in classroom management and active learning facilitation. The novelty of this program lies in reconstructing a competitive format into a pedagogical device that integrates cooperative learning principles and service learning within a community-based partnership. This model provides a replicable framework for character-oriented and experiential physical education practices.